Peran Mahasiswa Pengelolaan Pembelajaran (PP) Program Studi PPKn sebagai Guru Pengganti dalam Meningkatkan Motivasi Belajar Siswa di SMAN 4 Kota Blitar - Parasuti, Devita Elok; Cahyani, Arik; erawanto, udin (LPPM Universitas Labuhanbatu, 2025)
This study aims to analyze the role of students of the Learning Management (PP) program of the Pancasila and Citizenship Education Study Program (PPKn) as substitute teachers in increasing student learning motivation at SMAN 4 Blitar City. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study show that before the presence of PP students, learning activities in the classroom tended to be conventional and monotonous, which had an impact on the low motivation of students to learn. After PP students attended and took over the role of substitute teachers, there was a positive change in learning patterns. PP students apply various methods that are more varied, interactive, and adaptive to the characteristics of Generation Z students, such as the use of digital media, group discussions, educational games, and contextual approaches. In addition, a more humane and non-rigid communication approach from PP students creates a more comfortable and open learning atmosphere. This change directly increases student participation, enthusiasm, and attendance in learning activities. Based on these findings, it can be concluded that PP students not only carry out the role of substitute teachers administratively, but also act as learning transformation agents who are able to build a positive and inspiring learning climate. This research contributes to the development of collaborative learning models and the strategic role of students in the world of secondary education.